Analysis of the Effect of Profitability Ratio, Liquidity Ratio, Solvency Ratio, and Activity Ratio on Stock Price (Empirical Study of Food and Beverage Companies Listed on the IDX 2020-2023) - Poejianto; Kurniawati, Lintang (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Stock prices are the values of a stock that describe the wealth of a company. Stock prices are essentially the acceptance of the amount of sacrifice that must be made by each investor for participation in the company. This study aims to analyze the effect of profitability ratios, liquidity ratios, Solvency ratios, and Activity ratios on stock prices in Food and Beverage companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used in this study was purposive sampling. A total of 100 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results of this study indicate that the Profitability ratio has a significant effect on stock prices. While the Liquidity ratio, Solvency ratio, Activity ratio do not have a significant effect on stock prices.